Cypsela morphology in the genus Nolletia (Asteraceae, Astereae) and a revision of the genus - Herman, Paul P.j. (Phytotaxa, 2013)
The genus Nolletia has never been revised. There is no key available to all the species, making identification extremely difficult and resulting in misidentifications. For only a few species there are fairly comprehensive species descriptions available. A complete revision of the genus was undertaken, a key to all the species was drawn up, full descriptions were made and distribution maps were provided. Five new species were described: N. annemarieae, N. annetjieae, N. vanhoepeniae, N. jeanettae and N. welmaniae. One southern African species (N. arenosa) is synonymized under N. chrysocomoides. The genus could be divided into two groups on the grounds of the cypsela morphology: one group has oblong epicarpic cells arranged in parallel rows, seen in surface view, while the other group has circular to elliptic epicarpic cells, seen in surface view. One species was reported to be poisonous to stock. It was previously identified as N. gariepina but is described here as one of the new species, N. vanhoepeniae.